THE ANALYSIS OF THE HUMAN RESOURCES MANAGEMENT IN THE ROMANIAN LEGAL SYSTEM FROM THE PERSPECTIVE OF THE COOPERATION AND VERIFICATION MECHANISM - VIORICA POPESCU (Challenges of the Knowledge Society)
At 1st January 2007 when Romania joined the European Union was established a Cooperation and Verification Mechanism (further named “CVM”) in order to support Romania to remedy certain shortcomings in the areas of judicial reform and fight against corruption, as well as to monitor the achieved progress through periodic reports. Though the reforms of the human resources management in the Romanian legal system were conceived in a coherent framework, the main changes in this area often did not complement each other, their implementation being sometimes inconsistent with previous measures taken. In this context, the study aims to make a short analysis of the way in which the human resources management’s reform was reflected in the European Commission’s reports, pointing the measures adopted by the Romanian authorities.